2008
DOI: 10.1007/s00330-008-1182-8
|View full text |Cite
|
Sign up to set email alerts
|

Ascending aorta measurements as assessed by ECG-gated multi-detector computed tomography: a pilot study to establish normative values for transcatheter therapies

Abstract: Ascending aorta measurements as assessed by ECG-gated multi-detector computed tomography: a pilot study to establish normative values for transcatheter therapies Abstract The aim of this study was to provide an insight into normative values of the ascending aorta in regards to novel endovascular procedures using ECG-gated multi-detector CT angiography. Seventy-seven adult patients without ascending aortic abnormalities were evaluated. Measurements at relevant levels of the aortic root and ascending aorta were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 37 publications
(22 reference statements)
2
31
0
1
Order By: Relevance
“…However, according to literature, variations of the annulus size during the cardiac cycle are limited [9,32], especially in patients with severe AS with severe calcifications of the aortic valve and the aortic wall and annulus. A previously published study establishing normative values for ascending aorta measurements found large inter-individual variations in diameters and distances but with limited intra-individual variations during the cardiac cycle [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to literature, variations of the annulus size during the cardiac cycle are limited [9,32], especially in patients with severe AS with severe calcifications of the aortic valve and the aortic wall and annulus. A previously published study establishing normative values for ascending aorta measurements found large inter-individual variations in diameters and distances but with limited intra-individual variations during the cardiac cycle [33].…”
Section: Discussionmentioning
confidence: 99%
“…4 The establishment of normative values and reference ranges, taking into account aging and gender, is of great importance for diagnosis, prognosis, serial monitoring, and determining the optimal timing for surgical intervention. Normal values and proximal aortic diameters have been reported using different imaging techniques, from the pioneer studies based on M-mode and 2D echocardiography 9,10 to more recent studies obtained using CT 7,8,20,[23][24][25] and MRI. 5,26 Despite differences in image acquisition methods, temporal and spatial resolution, and signal-to-noise ratios, CT, MRI, TTE, and transesophageal echocardiography (TEE) have evolved as near equal standards for assessing aortic root size.…”
Section: Normal Aortic Dimensionsmentioning
confidence: 97%
“…Thus, CT allows for an accurate assessment of coronary arteries [15][16][17] and aortic root morphology [18,19].…”
Section: Introductionmentioning
confidence: 99%